GM-CSF and IL-3 Modulate Human Monocyte TNF-α Production and Renewal in In Vitro Models of Trained Immunity - Borriello, Francesco; Iannone, Raffaella; Di Somma, Sarah; Loffredo, Stefania; Scamardella, Eloise; Galdiero, Maria Rosaria; Varricchi, Gilda; Granata, Francescopaolo; Portella, Giuseppe; Marone, Gianni (Frontiers in Immunology, 2017)
GM-CSF and IL-3 are hematopoietic cytokines that also modulate the effector functions of several immune cell subsets. In particular, GM-CSF and IL-3 exert a significant control on monocyte and macrophage effector functions, as assessed in experimental models of inflammatory and autoimmune diseases and also human studies. Here we sought to investigate the mechanisms and the extent to which GM-CSF and IL-3 modulate the pro-inflammatory, LPS-mediated, activation of human CD14+ monocytes taking into account the new concept of trained immunity (i.e. the priming stimulus modulates the response to subsequent stimuli mainly by inducing chromatin remodelling and increased transcription at relevant genetic loci). We demonstrate that GM-CSF and IL-3 priming enhances TNF-α production upon subsequent LPS stimulation (short-term model of trained immunity) in a p38- and SIRT2-dependent manner without increasing TNF primary transcript levels (a more direct measure of transcription), thus supporting a post-transcriptional regulation of TNF-α in primed monocytes. GM-CSF and IL-3 priming followed by 6 days of resting also results in increased TNF-α production upon LPS stimulation (long-term model of trained immunity). In this case, however, GM-CSF and IL-3 priming induces a c-Myc-dependent monocyte renewal and increase in cell number that is in turn responsible for heightened TNF-α production. Overall, our results provide insights to understand the biology of monocytes in health and disease conditions in which the hematopoietic cytokines GM-CSF and IL-3 play a role and also extend our knowledge of the cellular and molecular mechanisms of trained immunity.